KARAKTERISTIK PERAIRAN DALAM KAITANNYA DENGAN PENGEMBANGAN USAHA PERIKANAN PELAGIS BESAR DI KABUPATEN ACEH JAYA - Mustaruddin Mustaruddin; Nasruddin Nasruddin; Sadarun Sadarun; Firman Kurniawan; Mulyono S. Baskoro (Institut Pertanian Bogor, 2011)
Big pelagic fishing represents main economic resources of coastal communities in Aceh Jaya Regency. But earthquake cycle and tsunami in 2004 have altered a lot of matter, inclusive characteristic of territorial water which is more or less influencing the production of big pelagic fish. This research aim to analyse of the chemical and physical characteristics of territorial water, its influence to the production of big pelagic fish, analyse of elegibility of its development The methods of research are chemistry and physics analysis, curve estimation analysis, and cost-benefit analysis. Territorial water of Aceh Jaya Regency has good category of DO, turbidity, Pb, brightness, current speed, and temperature, and also good enough category of nitrate and TSS. DO and nitrate have positive correlation significantly to the production of big pelagic fish, but it’s not so effective if DO condition very high (> 8,25 ppm), while about nitrate, more effective if nitrate condition > 0,0065 ppm. TSS has positive correlation to the production of big pelagic fish in territorial water of Aceh Jaya Regency, but temperature tend to negativity. Big pelagic fishing (purse seine, gillnet, and trolling line) are eligible to developed in that location, where NPV value of each are Rp 4.021.356.705, Rp 505.226.479, and Rp 375.453.615, and B/C ratio of them are according to standard.